2020
DOI: 10.1101/2020.04.08.20057463
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 epidemic in Malaysia: Impact of lockdown on infection dynamics

Abstract: COVID-19 epidemic in Malaysia started as a small wave of 22 cases in January 2020 through imported cases. It was followed by a bigger wave mainly from local transmissions resulting in 651 cases. The following wave saw unexpectedly three digit number of daily cases following a mass gathering urged the government to choose a more stringent measure. A limited lock-down approach called Movement Control Order (MCO) was immediately initiated to the whole country as a way to suppress the epidemic trajectory. The lock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 12 publications
(14 reference statements)
0
59
0
5
Order By: Relevance
“…Evidence that facemasks can protect against infections in the community is relatively scare[40][41][42], as acknowledged by contrasting views on medical facemasks by governments and public health experts[20]. An epidemic forecasting models was used by Salim, Naomie, et al to estimate the number of positive COVID-19 in Malaysia estimated that the peak will be on 19 April 2020 with an estimation of 5,637 positive cases[43], however 5,425 positive cases[44]were reported on the same date questioning the effectiveness of facemask in reducing infection . As evidence suggests COVID-19 could be transmitted through droplet[45,46], surgical masks may be ineffective for prevention as they generally do not form a tight seal against the face skin and hence are not endorsed to protect people from airborne infectious as the infection could happen through the mucous membranes of the eyes[47].Nonetheless , two community based retrospective case-control studies in Hong Kong and China during previous 2003 SARS-CoV-1 outbreak reported that use of medical grade facemasks (surgical masks in both studies) was associated with at least 60% lower odds of contracting SARS[48,49].…”
mentioning
confidence: 99%
“…Evidence that facemasks can protect against infections in the community is relatively scare[40][41][42], as acknowledged by contrasting views on medical facemasks by governments and public health experts[20]. An epidemic forecasting models was used by Salim, Naomie, et al to estimate the number of positive COVID-19 in Malaysia estimated that the peak will be on 19 April 2020 with an estimation of 5,637 positive cases[43], however 5,425 positive cases[44]were reported on the same date questioning the effectiveness of facemask in reducing infection . As evidence suggests COVID-19 could be transmitted through droplet[45,46], surgical masks may be ineffective for prevention as they generally do not form a tight seal against the face skin and hence are not endorsed to protect people from airborne infectious as the infection could happen through the mucous membranes of the eyes[47].Nonetheless , two community based retrospective case-control studies in Hong Kong and China during previous 2003 SARS-CoV-1 outbreak reported that use of medical grade facemasks (surgical masks in both studies) was associated with at least 60% lower odds of contracting SARS[48,49].…”
mentioning
confidence: 99%
“…Second, literature has suggested that the doubling time of seven days is a signal for public health intervention to be done swiftly to reduce the transmission. 23 Due to the data-driven nature of this analysis, the forecasting of new cases should be carefully interpreted. This is based on new cases but not based on case date of onset, which can tell much more about the dynamics of the disease.…”
Section: -Day Forecast Using Expert Modelermentioning
confidence: 99%
“…4 The effect of the MCO has shown a reducing trend in incidence cases. 5 This has prompted the government to loosen the MCO before eventually lifting the order. 4 Many studies have used mathematical modelling to predict the dynamic of this pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Such explosive COVID-19 pandemic in Malaysia has called for pragmatic preventive measures to be implemented, including intensive case diagnosis, precise tracking, and compulsory two-week quarantine. Therefore, the Malaysian government has declared the enforcement of the Movement Control Order (MCO) as the strategy of flattening the pandemic curve [2].…”
Section: Introductionmentioning
confidence: 99%